Manufacturing method of thermal spraying protective coating of automobile exhaust nitrogen-oxygen sensor chip and product

By using spherical high-purity alumina raw materials and ultrasonic assisted technology, combined with screen printing and plasma spraying, a protective coating of automotive exhaust nitrogen oxygen sensor chip with high porosity, good heat resistance and breathability was prepared, and the current solution was solved. There are problems of poor adhesion of coatings and difficult shape control, which achieves more efficient thermal shock buffering and pollutant barrier effects.

CN119392152APending Publication Date: 2025-02-07DEQING CHUANGZHI TECH CO LTD

Patent Information

Application Number
CN202411396879.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing automotive exhaust nitrogen oxygen sensor chip protective coating process has problems such as poor adhesion, uneven thickness and difficult to control shape. It is difficult to effectively buffer the thermal shock impact caused by high temperature and water vapor, and block pollutants in the exhaust gas.

Method used

The spherical high-purity alumina raw material is prepared by ultrasonic assist, combined with screen-printed alumina transition coating and high pore bonding layer, and the coating of heat-dissipating graphene nanosheets/polyolefin elastomer films is prepared with Protective coating with high porosity and good heat resistance and breathability.

Benefits of technology

It improves the adhesion and shape control of the coating, enhances the tolerance to high temperature and water vapor, effectively blocks pollutants in the exhaust gas, extends the working life of the sensor and improves its performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392152A_ABST
    Figure CN119392152A_ABST
Patent Text Reader

Abstract

The invention relates to a manufacturing method of a thermal spraying protective coating of an automobile exhaust nitrogen-oxygen sensor chip, which comprises the steps of spherical high-purity aluminum oxide raw material powder preparation, chip pretreatment, high-porosity bonding layer preparation, plasma spraying, heat dissipation graphene nanosheet / polyolefin elastomer film preparation, coating and the like. According to the invention, a chip is used as a substrate, and a silk-screen printing aluminum oxide transition coating is added in chip pretreatment, so that the prepared product is uniform and reliable in coating and high in binding force, a high-pore structure balances thermal shock influence caused by water vapor, invasion of pollutants is blocked under the condition that air permeability is not influenced, the working state of the sensor is improved, and the service life of the sensor is prolonged. The method has great significance in the field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coating preparation, and in particular to a method for preparing a thermal spray protective coating for an automobile exhaust nitrogen and oxygen sensor chip. Background Art

[0002] The nitrogen oxide sensor is used to detect nitrogen oxides (NO x ) concentration and oxygen (O2) concentration, monitor and feedback the engine combustion and three-way catalytic state, achieve full combustion and effectively reduce the emission of pollutants in the exhaust gas. The sensor chip adopts the HTCC zirconium oxide ceramic substrate multi-chamber structure design, with a built-in platinum detection electrode. It uses the high-temperature electrolyte characteristics of zirconium oxide to detect the concentration difference potential formed by the oxygen ion concentration difference in each chamber, so that the ECU can calculate the change in oxygen content and control the engine combustion state. A heating circuit is set inside the sensor chip. When working, the chip detection position is heated to 500-800℃ to reach the working temperature of zirconium oxide oxygen conduction. Due to the use of a multi-chamber cavity structure, the overall structural strength and thermal shock resistance of the chip are relatively weak. The water vapor generated in the automobile exhaust will inevitably cause a certain thermal shock impact on the chip, causing microcracks or even fractures inside the chip. In addition, there are also pollutants such as engine oil, refrigerant, etc. mixed in the exhaust gas and incomplete combustion, which enter the detection cavity through the gas inlet, causing electrode poisoning and unable to work normally. Therefore, it is necessary to make a protective coating on the working part of the chip. The coating needs to withstand working under high temperature, buffer the thermal shock caused by moisture, and block the pollution of exhaust pollutants to the electrode without affecting the permeability of the gas channel.

[0003] In a published patent 202111150011.4, a ceramic slurry pulling, dipping and sintering method is used to make an anti-dew point protective coating. This process has some problems: 1. The slurry is prone to cracking after drying; 2. The coating has poor adhesion after sintering and is easy to fall off; 3. The thickness is uneven and the shape is difficult to control. The above problems still need to be improved. Summary of the invention

[0004] The technical purpose of the present invention is to solve the problems in the background technology and provide a method for preparing a thermal spray protective coating for an automobile exhaust nitrogen and oxygen sensor chip.

[0005] The above technical objectives of the present invention are achieved through the following technical solutions: A method for preparing a thermal spray protective coating for an automobile exhaust nitrogen and oxygen sensor chip comprises the following preparation steps: Step S1: Preparation of spherical high-purity alumina raw material powder: The spherical high-purity alumina is prepared by a spray granulation method; Step S2: Chip pretreatment: The chip needs to be screen-printed with an outer aluminum oxide transition coating. The aluminum oxide transition coating uses a metal mesh filler sol-gel aluminum oxide coating. The coating includes a metal alkoxide precursor, an adhesive, an acid catalyst and pure water. The prepared coating is then screen-printed onto the chip. This process is embedded in the chip manufacturing process and does not need to be repeated independently. Step S3: Preparation of high-porosity bonding layer: The bonding layer material includes aluminum oxide, boric acid, sodium carbonate, and water glass. The high-porosity aluminum oxide coating prepared from the above materials is then mixed with aluminum sol and deionized water in a certain proportion to obtain the high-porosity bonding layer coating; Step S4: plasma spraying of high-porosity bonding layer coating: plasma spraying of the high-porosity bonding layer coating prepared in step S3 on the chip; Step S5: Preparation and coating of heat dissipating graphene nanosheets / polyolefin elastomer film: The graphene nanosheets and polyolefin elastomer are mixed in proportion, preheated, and then extruded to obtain the graphene nanosheets / polyolefin elastomer film and coated on the chip after plasma spraying in step S4, thereby obtaining a thermal spray protective coating for automobile exhaust nitrogen oxide sensor chip.

[0006] Preferably, the raw materials for preparing the spherical high-purity alumina raw material in step S1 also include tetramethylammonium hydroxide.

[0007] Preferably, the process of preparing high-purity spherical alumina with ultrasound assistance is to mix tetramethylammonium hydroxide with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 80-90°C and 35-45kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 40-60°C and calcined at 1200-1300°C to obtain the high-purity alumina powder.

[0008] The advantage of adopting the present invention is that the spherical high-purity alumina raw material in the present invention is prepared in pure water with the assistance of ultrasound and the addition of tetramethylammonium hydroxide. The spherical ultrafine high-purity alumina prepared by this method can destroy the gas barrier film in the early stage of the reaction by ultrasound, thereby increasing the reaction potential energy of the aluminum surface, accelerating the reaction rate, and improving the dissociation rate of the corresponding crystal face crystals. Not only can high-purity spherical alumina with a purity of more than 99.999% and extremely few impurities be obtained, but the obtained alumina particle size is below 350nm, and its fine particle size is of great benefit to the preparation of the coating in the present invention.

[0009] Preferably, in step S2, the metal alkoxide precursor is aluminum isopropoxide, the binder is polyethyleneimine, and the acid catalyst is hydrochloric acid.

[0010] Preferably, the preparation process of the alumina transition coating is as follows: add excess pure water to the metal alkoxide precursor at a temperature of 75±10°C for hydrolysis, set the rotation speed to 720-800rpm, then add hydrochloric acid dropwise for catalytic hydrolysis and continue to stir the mixture under the same conditions until the solution becomes transparent, take the mixed product and age it at the same temperature for later use; at the same time, prepare a metal mesh filler, wash it with alkali for 30 minutes, immerse it in the above mixture solution at a constant speed, and finally calcine it at 450-500°C for 1h to form a continuous α-Al2O3 film. In the above process, the molar ratio of Al / HCl / H2O is 1:(1-5):100; the obtained film is screen-printed onto the chip to obtain the pre-treated chip.

[0011] The advantage of adopting the present invention is that the metal alkoxide precursor and the acid catalyst are hydrolyzed in pure water to prepare the screen printing coating, which can form an alumina sol screen printing coating with controllable high adhesion on the metal screen filler and has good heat resistance, which is of great significance for applying it to nitrogen oxide sensor chips.

[0012] The present invention has the following advantages: (1) the thickness of the ceramic film layer can be controlled within a few microns, and the template grains in a single film layer can be well oriented under the action of shear force; (2) in the absence of a template, high-textured ceramics can also be prepared by the principle of multi-layer grain growth; (3) the slurry preparation and printing process are simple, the prepared slurry has a long service life, good stability and low cost; (4) it can be used for the preparation of gradient materials. The preparation of textured ceramics by the screen printing multi-layer grain growth method can maintain the original properties of the material while significantly improving the necessary properties in a specific direction, providing a broad development platform for the practical application of ceramic materials.

[0013] The invention has the advantages that the prepared screen printing film coating has a thickness of 5-10 um and a surface roughness Ra of 1.5-2.0.

[0014] Preferably, the alumina in the raw material of step S3 is the spherical high-purity alumina prepared in step S1, the water glass is an aqueous solution of sodium silicate, and the raw material also includes a small amount of carbon powder; the mass fraction of the alumina is 90-93 parts, the mass fraction of the boric acid is 0.5-0.85 parts, the mass fraction of the sodium carbonate is 0.1-0.5 parts, the mass fraction of the water glass is 0.5-0.85 parts, and the rest is carbon powder.

[0015] Preferably, the preparation process of the high-porosity bonding layer slurry is as follows: after mixing the above raw materials in proportion, add deionized water with a mass of 7-8% of the total weight of the mixture, knead and mix, and compact into blocks under a uniaxial press at 100MPa, and heat the obtained blocks in a reducing atmosphere containing carbon powder for 1h at a temperature of 1650-1800°C and a heating rate of 100°C / h to burn off excess carbon and obtain porous alumina, which is crushed and ground to obtain high-porosity porous alumina with a particle size distribution range of 25-53um.

[0016] The advantage of adopting the present invention is that the heat resistance and mechanical strength of the high-porosity alumina slurry prepared by the method can be improved by 1.5-2 times compared with ordinary alumina slurry; in addition, the spherical high-purity alumina prepared in step S1 of the scheme of the present invention is further used in the raw material to bring higher porosity adhesion, uniform thickness, controllable shape, and high coating bonding strength.

[0017] Preferably, the obtained high porosity porous alumina is mixed with deionized water and aluminum sol to obtain the high porosity bonding layer slurry, wherein the mass fraction of the high porosity porous alumina is 85-90 parts, the mass fraction of the aluminum sol is 5-10 parts, and the rest is deionized water.

[0018] The advantage of adopting the present invention is that the porosity of the prepared high-porosity alumina slurry reaches 20%-40%, which can block the invasion of pollutants without affecting the air permeability, thereby improving the working state and life of the sensor.

[0019] Preferably, during the plasma spraying process in step S4, the chip is mounted on a rotating table, the speed during spraying is 200-500 rpm, the spray gun beam scans and sprays the chip surface at an angle of 10-45°, the plasma spray gun is a 40KW internal powder feeding spray gun, the spraying parameters are current 500-600A, voltage 55-65V, main gas flow rate 35-45NLPM, secondary gas flow rate 5-8NLPM, powder feeding amount 20-40g / min, spraying distance 100-150mm, coating thickness 0.35-0.5mm.

[0020] The advantage of adopting the present invention is that after adjusting the spraying parameters, the ceramic powder can be melted in a limited manner in the flame of the spray gun, and combined with the change of the spraying beam angle, a controllable shielding effect can be achieved to achieve a high porosity distribution.

[0021] Preferably, the heat dissipating graphene nanosheet / polyolefin elastomer film preparation process in step S5 is: mixing graphene nanosheet particles and polyolefin elastomer particles, wherein the mass fraction of graphene nanosheets is 0.25-1 part, and the rest is polyolefin elastomer, then filtering the above mixed particles through a 200μm sieve to remove excess graphene nanosheets, preheating the filtered mixed powder at 50-100℃ for 10-20min, and finally hot pressing at 100-130℃ and 12MPa to obtain the heat dissipating graphene nanosheet / polyolefin elastomer film.

[0022] The advantages of adopting the present invention are that the tensile strength, elongation at break and adhesion of the prepared graphene / polyolefin elastomer film are as good as those of commercial thermal interface material products; the prepared graphene / polyolefin elastomer film can be used as a thermal interface material for chip heat dissipation, and has a good heat dissipation effect; in addition, the prepared GNP / POE film can be peeled off from the chip without residue after the chip operation is completed, which is of great significance to actual production.

[0023] In summary, the present invention has the following beneficial effects: 1. By optimizing the spherical production process of high-purity alumina in the pre-production process and utilizing the ultrasound-assisted tetramethylammonium hydroxide preparation process, the spherical ultrafine high-purity alumina prepared by this method can destroy the gas barrier film at the initial stage of the reaction, thereby increasing the reaction potential energy of the aluminum surface, accelerating the reaction rate, and improving the dissociation rate of the corresponding crystal face crystals. Not only can high-purity spherical alumina with a purity of more than 99.999% and extremely few impurities be obtained, but also the obtained alumina particle size is less than 350nm, and its fine particle size is of great benefit to the slurry preparation in the present invention; 2. By using the chip pre-treatment screen printing alumina transition coating in step S2 of the scheme of the present invention, the screen printing coating is prepared by hydrolyzing the metal alkoxide precursor and the acid catalyst in pure water, so that the alumina sol screen printing coating with controllable high adhesion can be formed on the metal screen filler; 3. By adding a high-porosity bonding layer to the invention scheme, and further using the spherical high-purity alumina prepared in step S1 in the process of preparing the high-porosity bonding layer, the porosity is as high as 20%-40%, which can block the invasion of pollutants without affecting the air permeability, so that the working state and life of the sensor are improved; and the thickness is uniform, the shape is controllable, the coating has high bonding strength, and the high temperature resistance and air permeability are good; 4. Through plasma spraying of high-porosity bonding layer, the spraying parameters are adjusted to make the ceramic powder melt in the flame of the spray gun to a limited extent, and combined with the change of the spraying beam angle, a controllable shielding effect is achieved to achieve high-porosity distribution; 5. A heat dissipation graphene nanosheet / polyolefin elastomer film is further coated on the outermost end of the coating. The prepared graphene / polyolefin elastomer film can be used as a thermal interface material for chip heat dissipation and has a good heat dissipation effect. In addition, the prepared GNP / POE film can be peeled off from the chip without residue after the chip operation is completed, which is of great significance to actual production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] FIG. 1 is a flow chart of a method for manufacturing a thermal spray protective coating for an automobile exhaust nitrogen and oxygen sensor chip. DETAILED DESCRIPTION

[0025] The following specific embodiments are merely explanations of the present invention and are not limitations of the present invention. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, such modifications are protected by the patent law as long as they are within the scope of the claims of the present invention.

[0026] It should be noted that the most suitable step S1 process for this scheme is determined by experiments as follows: the spherical high-purity aluminum oxide is obtained by ultrasonicating aluminum powder in ultrapure water: tetramethylammonium hydroxide is mixed with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, then aluminum powder is added, wherein the aluminum powder has an Al content of >99.999%, and the solution is reacted at 90°C and 40kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 50°C and calcined at 1250°C to obtain the high-purity alumina powder. Therefore, the parameters in step S1 above are used in the following embodiments for experiments. Example 1

[0027] Step S1: Preparation of spherical high-purity alumina raw material powder: The spherical high-purity alumina is obtained by ultrasonication of aluminum powder in ultrapure water: Tetramethylammonium hydroxide is mixed with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 90°C and 40kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 50°C and calcined at 1250°C to obtain the high-purity alumina powder.

[0028] Step S2 chip pretreatment: The chip needs to be screen-printed with an outer alumina transition coating. The metal alkoxide precursor is hydrolyzed by adding excess pure water at a temperature of 75°C, the rotation speed is set to 720rpm, and then hydrochloric acid is added dropwise to catalyze the hydrolysis and the mixture is continued to be stirred under the same conditions until the solution becomes transparent. The mixed product is aged at the same temperature for later use; at the same time, a metal mesh filler is prepared and alkaline washed for 30 minutes, and then immersed in the above mixture solution at a constant speed, and finally calcined at 450°C for 1h to form a continuous α-Al2O3 film. In the above process, the molar ratio of Al / HCl / H2O is 1:1:100; the obtained film is screen-printed onto the chip to obtain the pre-treated chip; this process is embedded in the chip manufacturing process and does not need to be repeated independently.

[0029] Step S3 Preparation of high-porosity bonding layer: The bonding layer materials include aluminum oxide, boric acid, sodium carbonate, and water glass; the mass fraction of the aluminum oxide is 90 parts, the mass fraction of the boric acid is 0.5 parts, the mass fraction of the sodium carbonate is 0.1 parts, the mass fraction of the water glass is 0.5 parts, and the rest is carbon powder. After the above raw materials are mixed in proportion, deionized water with a mass of 7% of the total weight of the mixture is added, and the mixture is kneaded and compacted into blocks under a uniaxial press of 100MPa to obtain The pressed block is heated in a reducing atmosphere containing carbon powder for 1 hour at a temperature of 1650°C and a heating rate of 100°C / h to burn off excess carbon and obtain porous alumina, which is crushed and ground to obtain high-porosity porous alumina with a particle size distribution range of 25-53um; the obtained high-porosity porous alumina is mixed with deionized water and aluminum sol to obtain the high-porosity bonding layer slurry, wherein the mass fraction of the high-porosity porous alumina is 85 parts, the mass fraction of the aluminum sol is 10 parts, and the rest is deionized water.

[0030] Step S4 plasma spraying of high-porosity bonding layer coating: the chip is installed on a rotating table, the speed during spraying is 200 rpm, the spray gun beam scans and sprays the chip surface at an angle of 10-45°, the plasma spray gun is a 40KW internal powder feeding spray gun, the spraying parameters are current 500-600A, voltage 55-65V, main gas flow rate 35-45NLPM, secondary gas flow rate 5-8NLPM, powder feeding amount 20g / min, spraying distance 100mm, coating thickness 0.35mm.

[0031] Step S5 preparation and coating of heat dissipating graphene nanosheets / polyolefin elastomer film: graphene nanosheet particles and polyolefin elastomer particles are mixed, wherein the mass fraction of graphene nanosheets is 0.25 parts and the rest is polyolefin elastomer, and then the mixed particles are filtered through a 200 μm sieve to remove excess graphene nanosheets, and the filtered mixed powder is preheated at 100° C. for 10 min, and finally hot-pressed at 100° C. and 12 MPa to obtain the heat dissipating graphene nanosheets / polyolefin elastomer film, and the graphene nanosheets / polyolefin elastomer film obtained by the above process is coated on the chip after plasma spraying in step S4, so as to obtain a thermal spray protective coating for an automobile exhaust nitrogen oxide sensor chip. Example 2

[0032] Step S1: Preparation of spherical high-purity alumina raw material powder: The spherical high-purity alumina is obtained by ultrasonication of aluminum powder in ultrapure water: Tetramethylammonium hydroxide is mixed with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 90°C and 40kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 50°C and calcined at 1250°C to obtain the high-purity alumina powder.

[0033] Step S2 chip pretreatment: The chip operation requires screen printing of an outer alumina transition coating. The metal alkoxide precursor is hydrolyzed by adding excess pure water at a temperature of 85°C, the rotation speed is set to 800rpm, and then hydrochloric acid is added dropwise to catalyze the hydrolysis and the mixture is continued to be stirred under the same conditions until the solution becomes transparent. The mixed product is aged at the same temperature for later use; at the same time, a metal mesh filler is prepared and alkaline washed for 30 minutes, and then immersed in the above mixture solution at a constant speed, and finally calcined at 500°C for 1h to form a continuous α-Al2O3 film. In the above process, the molar ratio of Al / HCl / H2O is 1:5:100; the obtained film is screen-printed onto the chip to obtain the pre-treated chip; this process is embedded in the chip manufacturing process and does not need to be repeated independently.

[0034] Step S3: Preparation of high-porosity bonding layer: The bonding layer materials include aluminum oxide, boric acid, sodium carbonate, and water glass; the mass fraction of the aluminum oxide is 93 parts, the mass fraction of the boric acid is 0.85 parts, the mass fraction of the sodium carbonate is 0.5 parts, the mass fraction of the water glass is 0.85 parts, and the rest is carbon powder. After mixing the above raw materials in proportion, add deionized water with a mass of 8% of the total weight of the mixture, stir and mix, and then compact into blocks under a uniaxial press at 100MPa. The obtained compact is heated in a reducing atmosphere containing carbon powder for 1 hour at a temperature of 1800°C and a heating rate of 100°C / h to burn off excess carbon and obtain porous alumina, which is crushed and ground to obtain high-porosity porous alumina with a particle size distribution range of 25-53um; the obtained high-porosity porous alumina is mixed and stirred with deionized water and aluminum sol to obtain the high-porosity bonding layer slurry, wherein the mass fraction of the high-porosity porous alumina is 90 parts, the mass fraction of the aluminum sol is 5 parts, and the rest is deionized water.

[0035] Step S4 plasma spraying of high-porosity bonding layer coating: the chip is installed on a rotating table, the speed during spraying is 500 rpm, the spray gun beam scans and sprays the chip surface at an angle of 18-45°, the plasma spray gun is a 40KW internal powder feeding spray gun, the spraying parameters are current 500-600A, voltage 55-65V, main gas flow rate 35-45NLPM, secondary gas flow rate 5-8NLPM, powder feeding amount 20g / min, spraying distance 150mm, coating thickness 0.5mm.

[0036] Step S5: Preparation and coating of heat dissipating graphene nanosheets / polyolefin elastomer film: Graphene nanosheet particles and polyolefin elastomer particles are mixed, wherein the mass fraction of graphene nanosheets is 1 part and the rest is polyolefin elastomer, and then the mixed particles are filtered through a 200 μm sieve to remove excess graphene nanosheets, and the filtered mixed powder is preheated at 50° C. for 20 min, and finally hot-pressed at 130° C. and 12 MPa to obtain the heat dissipating graphene nanosheets / polyolefin elastomer film, and the graphene nanosheets / polyolefin elastomer film obtained by the above process is coated on the chip after plasma spraying in step S4, so as to obtain a thermal spray protective coating for an automobile exhaust nitrogen oxide sensor chip. Example 3

[0037] Step S1: Preparation of spherical high-purity alumina raw material powder: The spherical high-purity alumina is obtained by ultrasonication of aluminum powder in ultrapure water: Tetramethylammonium hydroxide is mixed with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 90°C and 40kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 50°C and calcined at 1250°C to obtain the high-purity alumina powder.

[0038] Step S2 chip pretreatment: the chip needs to screen-print an outer alumina transition coating, add excess pure water to the metal alkoxide precursor at a temperature of 78°C for hydrolysis, set the rotation speed to 750rpm, then add hydrochloric acid to catalyze the hydrolysis and continue to stir the mixture under the same conditions until the solution becomes transparent, take the mixed product and age it at the same temperature for use; at the same time, prepare a metal mesh filler, wash it with alkali for 30 minutes, immerse it in the above mixture solution at a constant speed, and finally calcine it at 475°C for 1h to form a continuous α-Al2O3 film. In the above process, the molar ratio of Al / HCl / H2O is 1:4:100; the obtained film is screen-printed onto the chip to obtain the pre-treated chip; this process is embedded in the chip manufacturing process and does not need to be repeated independently.

[0039] Step S3: Preparation of high-porosity bonding layer: The bonding layer materials include aluminum oxide, boric acid, sodium carbonate, and water glass; the mass fraction of the aluminum oxide is 92.3 parts, the mass fraction of the boric acid is 0.6 parts, the mass fraction of the sodium carbonate is 0.33 parts, the mass fraction of the water glass is 0.56 parts, and the rest is carbon powder. After mixing the above raw materials in proportion, add deionized water with a mass of 7.5% of the total weight of the mixture, stir and mix, and then compact into blocks under a uniaxial press at 100 MPa. The obtained compact is heated in a reducing atmosphere containing carbon powder for 1 hour at a temperature of 1750°C and a heating rate of 100°C / h to burn off excess carbon and obtain porous alumina, which is crushed and ground to obtain high-porosity porous alumina with a particle size distribution range of 35-53um; the obtained high-porosity porous alumina is mixed with deionized water and aluminum sol to obtain the high-porosity bonding layer slurry, wherein the mass fraction of the high-porosity porous alumina is 89 parts, the mass fraction of the aluminum sol is 6.2 parts, and the rest is deionized water.

[0040] Step S4 plasma spraying of high-porosity bonding layer coating: the chip is installed on a rotating table, the speed during spraying is 395 rpm, the spray gun beam scans and sprays the chip surface at an angle of 28-45°, the plasma spray gun is a 40KW internal powder feeding spray gun, the spraying parameters are current 500-600A, voltage 55-65V, main gas flow rate 35-45NLPM, secondary gas flow rate 5-8NLPM, powder feeding amount 30g / min, spraying distance 125mm, coating thickness 0.42mm.

[0041] Step S5 preparation and coating of heat dissipating graphene nanosheets / polyolefin elastomer film: graphene nanosheet particles and polyolefin elastomer particles are mixed, wherein the mass fraction of graphene nanosheets is 0.5 parts and the rest is polyolefin elastomer, and then the mixed particles are filtered through a 200 μm sieve to remove excess graphene nanosheets, and the filtered mixed powder is preheated at 80° C. for 10-20 minutes, and finally hot-pressed at 120° C. and 12 MPa to obtain the heat dissipating graphene nanosheets / polyolefin elastomer film, and the graphene nanosheets / polyolefin elastomer film obtained by the above process is coated on the chip after plasma spraying in step S4, so as to obtain a thermal spray protective coating for automobile exhaust nitrogen oxide sensor chip. Example 4

[0042] Step S1: Preparation of spherical high-purity alumina raw material powder: The spherical high-purity alumina is obtained by ultrasonication of aluminum powder in ultrapure water: Tetramethylammonium hydroxide is mixed with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 90°C and 40kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 50°C and calcined at 1250°C to obtain the high-purity alumina powder.

[0043] Step S2 chip pretreatment: the chip needs to screen-print an outer alumina transition coating, add excess pure water to the metal alkoxide precursor at a temperature of 78°C for hydrolysis, set the rotation speed to 750rpm, then add hydrochloric acid to catalyze the hydrolysis and continue to stir the mixture under the same conditions until the solution becomes transparent, take the mixed product and age it at the same temperature for use; at the same time, prepare a metal mesh filler, wash it with alkali for 30 minutes, immerse it in the above mixture solution at a constant speed, and finally calcine it at 475°C for 1h to form a continuous α-Al2O3 film. In the above process, the molar ratio of Al / HCl / H2O is 1:3.5:100; the obtained film is screen-printed onto the chip to obtain the pre-treated chip; this process is embedded in the chip manufacturing process and does not need to be repeated independently.

[0044] Step S3: Preparation of high-porosity bonding layer: The bonding layer materials include aluminum oxide, boric acid, sodium carbonate, and water glass; the mass fraction of the aluminum oxide is 90.5 parts, the mass fraction of the boric acid is 0.5 parts, the mass fraction of the sodium carbonate is 0.48 parts, the mass fraction of the water glass is 0.75 parts, and the rest is carbon powder. After mixing the above raw materials in proportion, add deionized water with a mass of 7% of the total weight of the mixture, stir and mix, and then compact into blocks under a uniaxial press at 100 MPa. The obtained compact is heated in a reducing atmosphere containing carbon powder for 1 hour at a temperature of 1700°C and a heating rate of 100°C / h to burn off excess carbon and obtain porous alumina, which is crushed and ground to obtain high-porosity porous alumina with a particle size distribution range of 40-53um; the obtained high-porosity porous alumina is mixed with deionized water and aluminum sol to obtain the high-porosity bonding layer slurry, wherein the mass fraction of the high-porosity porous alumina is 86 parts, the mass fraction of the aluminum sol is 8 parts, and the rest is deionized water.

[0045] Step S4 plasma spraying of high-porosity bonding layer coating: the chip is installed on a rotating table, the speed during spraying is 450 rpm, the spray gun beam scans and sprays the chip surface at an angle of 35-45°, the plasma spray gun is a 40KW internal powder feeding spray gun, the spraying parameters are current 500-600A, voltage 55-65V, main gas flow rate 35-45NLPM, secondary gas flow rate 5-8NLPM, powder feeding amount 30g / min, spraying distance 115mm, coating thickness 0.36mm.

[0046] Step S5 preparation and coating of heat dissipating graphene nanosheets / polyolefin elastomer film: graphene nanosheet particles and polyolefin elastomer particles are mixed, wherein the mass fraction of graphene nanosheets is 0.75 parts and the rest is polyolefin elastomer, and then the mixed particles are filtered through a 200 μm sieve to remove excess graphene nanosheets, and the filtered mixed powder is preheated at 80° C. for 15 minutes, and finally hot-pressed at 120° C. and 12 MPa to obtain the heat dissipating graphene nanosheets / polyolefin elastomer film, and the graphene nanosheets / polyolefin elastomer film obtained by the above process is coated on the chip after plasma spraying in step S4, so as to obtain a thermal spray protective coating for automobile exhaust nitrogen oxide sensor chip. Example 5

[0047] Step S1: Preparation of spherical high-purity alumina raw material powder: The spherical high-purity alumina is obtained by ultrasonication of aluminum powder in ultrapure water: Tetramethylammonium hydroxide is mixed with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 90°C and 40kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 50°C and calcined at 1250°C to obtain the high-purity alumina powder.

[0048] Step S2 chip pretreatment: the chip needs to screen-print an outer alumina transition coating, add excess pure water to the metal alkoxide precursor at a temperature of 78°C for hydrolysis, set the rotation speed to 750rpm, then add hydrochloric acid to catalyze the hydrolysis and continue to stir the mixture under the same conditions until the solution becomes transparent, take the mixed product and age it at the same temperature for use; at the same time, prepare a metal mesh filler, wash it with alkali for 30 minutes, immerse it in the above mixture solution at a constant speed, and finally calcine it at 475°C for 1h to form a continuous α-Al2O3 film. In the above process, the molar ratio of Al / HCl / H2O is 1:4:100; the obtained film is screen-printed onto the chip to obtain the pre-treated chip; this process is embedded in the chip manufacturing process and does not need to be repeated independently.

[0049] Step S3 Preparation of high-porosity bonding layer: The bonding layer materials include aluminum oxide, boric acid, sodium carbonate, and water glass; the mass fraction of the aluminum oxide is 90-93 parts, the mass fraction of the boric acid is 0.55 parts, the mass fraction of the sodium carbonate is 0.2 parts, the mass fraction of the water glass is 0.72 parts, and the rest is carbon powder. After the above raw materials are mixed in proportion, deionized water with a mass of 7.3% of the total weight of the mixture is added, and the mixture is kneaded and compacted under a uniaxial press at 100MPa. The obtained pressed blocks are heated in a reducing atmosphere containing carbon powder for 1 hour at a temperature of 1780°C and a heating rate of 100°C / h to burn off excess carbon and obtain porous alumina, which are crushed and ground to obtain high-porosity porous alumina with a particle size distribution range of 47-53um; the obtained high-porosity porous alumina is mixed with deionized water and aluminum sol to obtain the high-porosity bonding layer slurry, wherein the mass fraction of the high-porosity porous alumina is 87 parts, the mass fraction of the aluminum sol is 9 parts, and the rest is deionized water.

[0050] Step S4 plasma spraying of high-porosity bonding layer coating: the chip is installed on a rotating table, the speed during spraying is 450 rpm, the spray gun beam scans and sprays the chip surface at an angle of 22-45°, the plasma spray gun is a 40KW internal powder feeding spray gun, the spraying parameters are current 500-600A, voltage 55-65V, main gas flow rate 35-45NLPM, secondary gas flow rate 5-8NLPM, powder feeding amount 20g / min, spraying distance 130mm, coating thickness 0.36mm.

[0051] Step S5: Preparation and coating of heat dissipating graphene nanosheets / polyolefin elastomer film: Graphene nanosheet particles and polyolefin elastomer particles are mixed, wherein the mass fraction of graphene nanosheets is 0.3 parts and the rest is polyolefin elastomer, and then the mixed particles are filtered through a 200 μm sieve to remove excess graphene nanosheets, and the filtered mixed powder is preheated at 80° C. for 15 minutes, and finally hot-pressed at 120° C. and 12 MPa to obtain the heat dissipating graphene nanosheets / polyolefin elastomer film, and the graphene nanosheets / polyolefin elastomer film obtained by the above process is coated on the chip after plasma spraying in step S4, so as to obtain a thermal spray protective coating for automobile exhaust nitrogen oxide sensor chip. Example 6

[0052] Step S1: Preparation of spherical high-purity alumina raw material powder: The spherical high-purity alumina is obtained by ultrasonication of aluminum powder in ultrapure water: Tetramethylammonium hydroxide is mixed with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 90°C and 40kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 50°C and calcined at 1250°C to obtain the high-purity alumina powder.

[0053] Step S2 chip pretreatment: the chip needs to screen-print an outer alumina transition coating, add excess pure water to the metal alkoxide precursor at a temperature of 78°C for hydrolysis, set the rotation speed to 750rpm, then add hydrochloric acid to catalyze the hydrolysis and continue to stir the mixture under the same conditions until the solution becomes transparent, take the mixed product and age it at the same temperature for use; at the same time, prepare a metal mesh filler, wash it with alkali for 30 minutes, immerse it in the above mixture solution at a constant speed, and finally calcine it at 475°C for 1h to form a continuous α-Al2O3 film. In the above process, the molar ratio of Al / HCl / H2O is 1:4:100; the obtained film is screen-printed onto the chip to obtain the pre-treated chip; this process is embedded in the chip manufacturing process and does not need to be repeated independently.

[0054] Step S3 Preparation of high-porosity bonding layer: The bonding layer materials include aluminum oxide, boric acid, sodium carbonate, and water glass; the mass fraction of the aluminum oxide is 93 parts, the mass fraction of the boric acid is 0.75 parts, the mass fraction of the sodium carbonate is 0.39 parts, the mass fraction of the water glass is 0.56 parts, and the rest is carbon powder. After the above raw materials are mixed in proportion, deionized water with a mass of 8% of the total weight of the mixture is added, and the mixture is kneaded and compacted into blocks under a uniaxial press at 100MPa to obtain The obtained pressed blocks are heated in a reducing atmosphere containing carbon powder for 1 hour at a temperature of 1800°C and a heating rate of 100°C / h to burn off excess carbon and obtain porous alumina, which is crushed and ground to obtain high-porosity porous alumina with a particle size distribution range of 35-50um; the obtained high-porosity porous alumina is mixed with deionized water and aluminum sol to obtain the high-porosity bonding layer slurry, wherein the mass fraction of the high-porosity porous alumina is 85.5 parts, the mass fraction of the aluminum sol is 6 parts, and the rest is deionized water.

[0055] Step S4 plasma spraying of high-porosity bonding layer coating: the chip is installed on a rotating table, the speed during spraying is 200-500 rpm, the spray gun beam scans and sprays the chip surface at an angle of 10-45°, the plasma spray gun is a 40KW internal powder feeding spray gun, the spraying parameters are current 500-600A, voltage 55-65V, main gas flow rate 35-45NLPM, secondary gas flow rate 5-8NLPM, powder feeding amount 35g / min, spraying distance 135mm, coating thickness 0.39mm.

[0056] Step S5 preparation and coating of heat dissipating graphene nanosheets / polyolefin elastomer film: graphene nanosheet particles and polyolefin elastomer particles are mixed, wherein the mass fraction of graphene nanosheets is 0.6 parts and the rest is polyolefin elastomer, and then the mixed particles are filtered through a 200 μm sieve to remove excess graphene nanosheets, and the filtered mixed powder is preheated at 50-100° C. for 15 minutes, and finally hot-pressed at 120° C. and 12 MPa to obtain the heat dissipating graphene nanosheets / polyolefin elastomer film, and the graphene nanosheets / polyolefin elastomer film obtained by the above process is coated on the chip after plasma spraying in step S4, so as to obtain a thermal spray protective coating for an automobile exhaust nitrogen oxide sensor chip. Comparative Example 1

[0057] Different from the above-mentioned embodiment, the comparative example does not use high-purity spherical alumina from the same source as that in the solution of the present invention, but uses common spherical alumina on the market.

[0058] Step S1 chip pretreatment: the chip needs to be screen-printed with an outer alumina transition coating. The metal alkoxide precursor is hydrolyzed by adding excess pure water at a temperature of 78°C, the rotation speed is set to 750rpm, and then hydrochloric acid is added dropwise to catalyze the hydrolysis and the mixture is continued to be stirred under the same conditions until the solution becomes transparent. The mixed product is aged at the same temperature for later use; at the same time, a metal mesh filler is prepared and alkaline washed for 30 minutes, and then immersed in the above mixture solution at a constant speed, and finally calcined at 475°C for 1h to form a continuous α-Al2O3 film. In the above process, the molar ratio of Al / HCl / H2O is 1:4:100; the obtained film is screen-printed onto the chip to obtain the pre-treated chip; this process is embedded in the chip manufacturing process and does not need to be repeated independently.

[0059] Step S2: Preparation of high-porosity bonding layer: The bonding layer materials include aluminum oxide, boric acid, sodium carbonate, and water glass; the mass fraction of the aluminum oxide is 92.3 parts, the mass fraction of the boric acid is 0.6 parts, the mass fraction of the sodium carbonate is 0.33 parts, the mass fraction of the water glass is 0.56 parts, and the rest is carbon powder. After mixing the above raw materials in proportion, add deionized water with a mass of 7.5% of the total weight of the mixture, stir and mix, and then compact into blocks under a uniaxial press at 100 MPa. The obtained compact is heated in a reducing atmosphere containing carbon powder for 1 hour at a temperature of 1750°C and a heating rate of 100°C / h to burn off excess carbon and obtain porous alumina, which is crushed and ground to obtain high-porosity porous alumina with a particle size distribution range of 35-53um; the obtained high-porosity porous alumina is mixed with deionized water and aluminum sol to obtain the high-porosity bonding layer slurry, wherein the mass fraction of the high-porosity porous alumina is 89 parts, the mass fraction of the aluminum sol is 6.2 parts, and the rest is deionized water.

[0060] Step S3 plasma spraying of high-porosity bonding layer coating: the chip is installed on a rotating table, the speed during spraying is 395 rpm, the spray gun beam scans and sprays the chip surface at an angle of 28-45°, the plasma spray gun is a 40KW internal powder feeding spray gun, the spraying parameters are current 500-600A, voltage 55-65V, main gas flow rate 35-45NLPM, secondary gas flow rate 5-8NLPM, powder feeding amount 30g / min, spraying distance 125mm, coating thickness 0.42mm.

[0061] Step S4: Preparation of heat dissipating graphene nanosheets / polyolefin elastomer film: Graphene nanosheet particles and polyolefin elastomer particles are mixed, wherein the mass fraction of graphene nanosheets is 0.5 parts and the rest is polyolefin elastomer, and then the mixed particles are filtered through a 200 μm sieve to remove excess graphene nanosheets, and the filtered mixed powder is preheated at 80° C. for 10-20 minutes, and finally hot-pressed at 120° C. and 12 MPa to obtain the heat dissipating graphene nanosheets / polyolefin elastomer film, and the graphene nanosheets / polyolefin elastomer film obtained by the above process is coated on the chip after plasma spraying in step S3, so as to obtain a thermal spray protective coating for an automobile exhaust nitrogen oxide sensor chip. Comparative Example 2

[0062] Different from the comparative example 1, this comparative example does not have a chip pre-treatment step, and directly performs subsequent protective coating. The parameters in the coating preparation and plasma spraying process are the same as those in the comparative example 1. Comparative Example 3

[0063] Different from the above-mentioned Example 3, this comparative example does not have the subsequent coating of the high-porosity adhesive layer and the heat-dissipating graphene nanosheet / polyolefin elastomer film, and the other parameters are the same as those of Example 3. Comparative Example 4

[0064] Different from the above-mentioned Example 3, this comparative example does not have the last step of coating the heat dissipating graphene nanosheets / polyolefin elastomer film. Comparative Example 5

[0065] Different from the above-mentioned Example 3, this comparative example does not have a coating of a high-porosity bonding layer.

[0066] The performance of the products of the above-mentioned embodiments 1-6 and comparative examples 1-6 was evaluated by conducting thermal cycle tests, moisture resistance tests, evaluating the heat dissipation effect, and observing the surface conditions of the chips. Comparative Example 6

[0067] This comparative example uses a common automobile exhaust nitrogen oxide sensor available on the market.

[0068] The thermal cycle experiment is as follows: during the experiment, the nitrogen oxygen sensor substrate is placed on the experimental table, and each thermal cycle is heated for 2.0 minutes with an 18V voltage and air-cooled for 3.0 minutes. The oxygen sensor substrate after the thermal cycle is packaged, and the oxygen signal of the nitrogen oxygen sensor and the bonding strength between the coating and the substrate are tested respectively; the nitrogen oxygen sensor signal measurement is carried out on a standard atmosphere test bench, and the bonding strength between the coating and the substrate is evaluated by the number of times the coating falls off during the impact test. During the test, the nitrogen oxygen sensor assembly is fixed on the base of the experimental table, and the pendulum is pulled up to deviate from the vertical direction at an angle of 60°, and then released from rest to hit the nitrogen oxygen sensor assembly. The coating shedding condition when the number of impacts is 45 is recorded, and 5 substrate samples are prepared for each embodiment or comparative example.

[0069] Moisture resistance test: The nitrogen oxide sensor substrate is placed in a high pressure and high humidity environment at 130°C and 85% relative humidity to evaluate its stability and reliability.

[0070] Heat dissipation effect: The above embodiments 1-6 and comparative examples 1-5 are ranked according to the effect of comparative example 6.

[0071] The results of 1000 thermal cycles of the embodiments and comparative examples are shown in Table 1 below: Table 1 Results of 1000 thermal cycle experiments

[0072] The results of 3000 thermal cycles of the embodiment and the comparative example are shown in Table 2 below: Table 2 Results of 3000 thermal cycle experiments

[0073] The results of 5000 thermal cycles of the embodiment and the comparative example are shown in Table 3 below: Table 3 Results of 5000 thermal cycle experiments

[0074] The results of 9000 thermal cycle experiments of the embodiment and the comparative example are shown in Table 4 below: Table 4 Results of 9000 thermal cycle experiments

[0075] Observation results of the moisture resistance experiment: the substrate products prepared in Examples 1-6 are very reliable and stable for a long time under the environment of 130°C and 85% relative humidity; Comparative Examples 4 and 5 are relatively stable, Comparative Examples 1-3 are slightly worse, and Comparative Example 6 is the most unstable.

[0076] Heat dissipation effect evaluation results: the heat dissipation effect is ranked as Example 3 > Example 4 > Example 5 > Example 6 > Example 1 > Example 2 > Comparative Example 4 > Comparative Example 5 > Comparative Example 1 > Comparative Example 2 > Comparative Example 3 > Comparative Example 6.

[0077] From the above results, we can draw the following conclusions: It can be seen from the data results in the table that the heat resistance, impact resistance, moisture resistance and heat dissipation effect of the automobile exhaust nitrogen oxide sensor chip coating prepared under the experimental conditions of Example 3 are the best among the above embodiments; Compared with Comparative Example 1, each embodiment has a greater impact on product performance because the high-purity spherical alumina prepared by the preparation method of the present invention is not used.

[0078] Compared with Comparative Examples 4 and 5, Comparative Example 4 has poor heat dissipation effect because the heat dissipation film in the solution of the present invention is not used; in Comparative Example 5, there is no coating of the high-porosity adhesive layer, and the adhesion, heat dissipation and heat resistance are all poor.

[0079] Compared with Comparative Examples 2 and 3, Comparative Example 2 has no chip processing, and Comparative Example 3 has no subsequent high-porosity adhesive layer and heat dissipation film. Its performance in all aspects cannot be compared with the results of the embodiment cases, and Comparative Example 6 is the worst.

Claims

1. A method for preparing a thermal spray protective coating for a vehicle exhaust nitrogen and oxygen sensor chip, characterized in that: The preparation method thereof comprises the following preparation steps: Step S1: Preparation of spherical high-purity alumina raw material powder: The spherical high-purity alumina is obtained by ultrasonicating aluminum powder in ultrapure water; Step S2: Chip pretreatment: The chip needs to be screen-printed with an outer aluminum oxide transition coating. The aluminum oxide transition coating uses a metal mesh filler sol-gel aluminum oxide coating. The coating includes a metal alkoxide precursor, an adhesive, an acid catalyst and pure water. The prepared coating is then screen-printed onto the chip. This process is embedded in the chip manufacturing process and does not need to be repeated independently; Step S3: Preparation of high-porosity bonding layer: The bonding layer material includes aluminum oxide, boric acid, sodium carbonate, and water glass. The high-porosity aluminum oxide coating prepared from the above materials is then mixed with aluminum sol and deionized water in a certain proportion to obtain the high-porosity bonding layer coating; Step S4: plasma spraying of high-porosity bonding layer coating: plasma spraying of the high-porosity bonding layer coating prepared in step S3 on the chip; Step S5: Preparation and coating of heat dissipating graphene nanosheets / polyolefin elastomer film: Graphene nanosheets and polyolefin elastomer are mixed in proportion, preheated and extruded to obtain a graphene nanosheet / polyolefin elastomer film, which is then coated on the chip after plasma spraying in step S4 to obtain a thermal spray protective coating for an automobile exhaust nitrogen oxide sensor chip.

2. The method for manufacturing a thermal spray protective coating for an automobile exhaust nitrogen and oxygen sensor chip according to claim 1, characterized in that: The raw materials for preparing the spherical high-purity alumina raw material in step S1 also include tetramethylammonium hydroxide.

3. The method for manufacturing a thermal spray protective coating for an automobile exhaust nitrogen and oxygen sensor chip according to claim 2, characterized in that: The process of preparing high-purity spherical alumina with ultrasound assistance is to mix tetramethylammonium hydroxide with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 80-90°C and 35-45kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 40-60°C and calcined at 1200-1300°C to obtain the high-purity alumina powder.

4. The method for manufacturing a thermal spray protective coating for an automobile exhaust nitrogen and oxygen sensor chip according to claim 1, characterized in that: In the step S2, the metal alkoxide precursor is aluminum isopropoxide, the binder is polyethyleneimine, and the acid catalyst is hydrochloric acid.

5. The method for manufacturing a thermal spray protective coating for an automobile exhaust nitrogen and oxygen sensor chip according to claim 4, characterized in that: The preparation process of the alumina transition coating is as follows: adding excess pure water to the metal alkoxide precursor at a temperature of 75±10°C for hydrolysis, setting the rotation speed to 720-800rpm, then dropping hydrochloric acid to catalyze the hydrolysis and continuing to stir the mixture under the same conditions until the solution becomes transparent, taking the mixed product and aging it under the same temperature conditions for use; at the same time, preparing a metal mesh filler, alkali-washing it for 30 minutes, immersing it in the above mixture solution at a constant speed, and finally calcining it at a temperature of 450-500°C for 1h to form a continuous α-Al2O3 film. In the above process, the molar ratio of Al / HCl / H2O is 1:(1-5):100; the obtained film is screen-printed onto a chip to obtain a pre-treated chip.

6. The method for manufacturing a thermal spray protective coating for an automobile exhaust nitrogen and oxygen sensor chip according to claim 1, characterized in that: The alumina in the raw material of step S3 is the spherical high-purity alumina prepared in step S1, the water glass is a sodium silicate aqueous solution, and the raw material also includes a small amount of carbon powder; the mass fraction of the alumina is 90-93 parts, the mass fraction of the boric acid is 0.5-0.85 parts, the mass fraction of the sodium carbonate is 0.1-0.5 parts, the mass fraction of the water glass is 0.5-0.85 parts, and the rest is carbon powder.

7. The method for manufacturing a thermal spray protective coating for an automobile exhaust nitrogen and oxygen sensor chip according to claim 6, characterized in that: The preparation process of the high-porosity bonding layer slurry is as follows: after mixing the above raw materials in proportion, adding deionized water with a mass of 7-8% of the total weight of the mixture, kneading and mixing, and compacting into blocks under a uniaxial press of 100MPa, heating the obtained blocks in a reducing atmosphere containing carbon powder for 1h at a temperature of 1650-1800°C and a heating rate of 100°C / h to burn off excess carbon and obtain porous alumina, and crushing and grinding to obtain high-porosity porous alumina with a particle size distribution range of 25-53um; The obtained high-porosity porous alumina is mixed with deionized water and aluminum sol to obtain the high-porosity bonding layer slurry, wherein the mass fraction of the high-porosity porous alumina is 85-90 parts, the mass fraction of the aluminum sol is 5-10 parts, and the rest is deionized water.

8. The method for manufacturing a thermal spray protective coating for an automobile exhaust nitrogen and oxygen sensor chip according to claim 1, characterized in that: During the plasma spraying process in step S4, the chip is mounted on a rotating table, the speed during spraying is 200-500 rpm, the spray gun beam scans and sprays the chip surface at an angle of 10-45°, the plasma spray gun is a 40KW internal powder feeding spray gun, the spraying parameters are current 500-600A, voltage 55-65V, main gas flow 35-45NLPM, secondary gas flow 5-8NLPM, powder feeding amount 20-40g / min, spraying distance 100-150mm, and coating thickness 0.35-0.5mm.

9. The method for manufacturing a thermal spray protective coating for an automobile exhaust nitrogen and oxygen sensor chip according to claim 1, characterized in that: The heat dissipation graphene nanosheet / polyolefin elastomer film preparation process in step S5 is as follows: graphene nanosheet particles and polyolefin elastomer particles are mixed, wherein the mass fraction of graphene nanosheets is 0.25-1 part, and the rest is polyolefin elastomer, and then the mixed particles are filtered through a 200 μm sieve to remove excess graphene nanosheets, and the filtered mixed powder is preheated at 50-100° C. for 10-20 min, and finally hot-pressed at 100-130° C. and 12 MPa to obtain the heat dissipation graphene nanosheet / polyolefin elastomer film.

10. A thermal spraying protective coating for a NOx sensor chip for automobile exhaust, characterized in that: The automotive exhaust nitrogen oxygen sensor chip thermal spray protective coating is prepared according to the manufacturing method of any one of claims 1 to 9, and can be applied to automotive nitrogen oxygen sensors for detecting fuel vehicle exhaust. It has high porosity, high heat dissipation rate and excellent high temperature resistance, can withstand working at high temperatures well, buffer the thermal shock caused by moisture, and block the pollution of exhaust pollutants to the electrode without affecting the gas channel permeability.

Citation Information

Patent Citations

  • Preparation method of dew-point-resistant protection coating for automobile oxygen sensor

    CN113845376A

Cited By

  • Preparation method of oxygen sensor protection layer and oxygen sensor

    CN120311128A